2017
DOI: 10.1182/blood-2016-07-728840
|View full text |Cite
|
Sign up to set email alerts
|

Rare genetic variants in SMAP1, B3GAT2, and RIMS1 contribute to pediatric venous thromboembolism

Abstract: Recent genome-wide association studies (GWAS) have confirmed known risk mutations for venous thromboembolism (VTE) and identified a number of novel susceptibility loci in adults. Here we present a GWAS in 212 nuclear families with pediatric VTE followed by targeted next-generation sequencing (NGS) to identify causative mutations contributing to the association. Three single nucleotide polymorphisms (SNPs) exceeded the threshold for genome-wide significance as determined by permutation testing using 100 000 boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This review mainly focuses on genes associated with primary VTE in adults and does not mention genetic factors contributing to other forms of VT, including cerebral vein thrombosis, splanchnic vein thrombosis and paediatric VTE. For example, a recent GWAS performed in paediatric VTE cases identified the B3GAT2 locus (Rühle et al , ) as a novel susceptibility locus for paediatric forms of VTE. Investigating this locus further in adults warrants effort.…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%
“…This review mainly focuses on genes associated with primary VTE in adults and does not mention genetic factors contributing to other forms of VT, including cerebral vein thrombosis, splanchnic vein thrombosis and paediatric VTE. For example, a recent GWAS performed in paediatric VTE cases identified the B3GAT2 locus (Rühle et al , ) as a novel susceptibility locus for paediatric forms of VTE. Investigating this locus further in adults warrants effort.…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%
“…These genes are involved in vesicle processing in blood cells, but need further functional studies to investigate the underlying biological mechanisms in VTE. Additionally, this study indicated the ABO locus, which determines the blood group and is a well‐established VTE risk factor in adults (Trégouët et al , ), to be also associated with paediatric VTE, albeit shortly missing genome‐wide significance (Rühle et al , ).…”
Section: Risk Factors For Paediatric Vtementioning
confidence: 87%
“…Variants residing in genes less obviously connected to coagulation pathways require hypothesis‐free genome‐wide approaches to be discovered. Recently, the first genome‐wide association study (GWAS) in paediatric VTE has been reported utilizing 212 affected offspring trios and complemented by next generation sequencing (Rühle et al , ). It revealed a new susceptibility region on chromosome 6 comprising the genes small ArfGAP 1 ( SMAP1 ), beta‐1,3‐glucuronyltransferase 2 ( B3GAT2 ) and regulating synaptic membrane exocytosis 1 ( RIMS1 ) (Rühle et al , ).…”
Section: Risk Factors For Paediatric Vtementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that genetic factors play a role in the occurrence of VTE [5] . A number of genes have been found to be susceptible to VTE occurrence [6,7] . Recently, some scholars have shown that immune gene mutations may provide new insights into the pathogenesis of VTE [8] .…”
Section: Introductionmentioning
confidence: 99%